The Influence of Positive Self-affirmation towards Malaysian ESL Students at Tertiary Level of Education - Philip, Evelyn; Philip, Alicia (International Journal of Humanities and Education Development (IJHED), 2022)
Positive self-affirmation when identified as value affirmation helps alleviate negative self threat among students’ when practiced in the right way which in turn boosts their self-esteem and thus motivation which eventually enables them to achieve an excellent result in their academic performance especially in the context of this study, the ESL reading classroom. Therefore, this study will be looking at the direct effect between positive self-affirmation, motivation and self-esteem towards ESL students’ academic performance in the ESL classroom and based on a review of several studies that was done previously on self-affirmation, motivation and self-esteem towards Malaysian ESL students’ academic performance, it was found out through a review on the results and discussion of previous studies that there is a positive significance between positive self-affirmation, self-esteem and motivation towards Malaysian ESL students’ academic performance in the ESL classroom.